New Variant of SARS-CoV-2 Dynamics with Imperfect Vaccine - Taye Samuel Faniran; Aatif Ali; Nawal E. Al-Hazmi; Joshua Kiddy K. Asamoah; Taher A. Nofal; Matthew O. Adewole (Complexity)
The occurrence of a new strain of SARS-CoV-2 cannot be ruled out. Therefore, this study seeks to investigate the possible effects of a hypothetical imperfect anti-COVID-19 vaccine on the control of not only the first variant of SARS-CoV-2 but also the second (new) variant of SARS-CoV-2. We further examine the rates r and a, escape of quarantined infectious individuals from isolation centers. The control Rc and basic reproduction numbers R0 are computed which gives assess to obtain asymptotic stability of disease-free equilibrium point globally and the existence of a unique persistent equilibrium solution. Numerical results reveal that people infected with the second strain who are vaccinated with an imperfect vaccine are under control but the prevalence of the second variant enhances the prevalence of the first variant. Thus, discovering a vaccine that is effective (to a good extent) for the prevention of variant 2 (new variant) is necessary for the control of COVID-19. Numerical results also reveal that increase in the rate at which individuals infected with the first variant escape the isolation center gives rise to the population infected with the first variant and lowers the peak of the population infected with the second variant. This is probably because individuals infected with the second variant appear to be more careful with their lives and get vaccinated more than individuals infected with the first variant.